Altered and conventional fractionated radiotherapy in locoregional control and survival of patients with squamous cell carcinoma of the larynx, oropharynx, and hypopharynx - Krstevska, Valentina; Crvenkova, Simonida (My University, 2006)
To compare the efficacy of two altered fractionation radiotherapy treatment protocols (hyperfractionation and accelerated fractionation with concomitant boost) with conventional fractionation in improvement of locoregional disease control and survival of patients with squamous cell carcinoma of the larynx, oropharynx, or hypopharynx.